Relevance of Communication to Risk in Disaster Management (American Journal of Management, 2023)
This article focuses on discussing the perception of risk and the approach to the problem of disaster management from the perspective of public policies, with special attention to communication strategies for prevention, information and intervention in the face of these phenomena.In order to analyze these issues from the point of view of political communication in its crisis and risk dimension, we will focus on disaster risk management and the role played by State policies and the media in such contexts.This implies the elaboration of a holistic view of the problem that allows adapting or modifying pre-existing behavioral patterns at all levels and social spheres in the face of risk.With this article we hope to contribute to the construction of knowledge linked to a particular area of public policy studies oriented to the production of indispensable communicative strategies in accordance with current needs in the field of disaster risk management, which may be taken as references by public organizations at different levels of the State.
Keywords: management; disaster management; risk communication; communication strategies; public information